Pengaruh Pemanfaatan Teknologi Informasi Dan Pengendalian Internal Terhadap Kualitas Laporan Keuangan Pada Rumah Sakit Umum Daerah Otanaha - Desi Setiowati; Sahmin Noholo; Hapsawati Taan (Program Pascasarjana STIE Amkop Makassar, 2025)
This study aims to examine the influence of Utilization of Information Technology and Internal Control on the Quality of Financial Statements at RSUD Otanaha. The research employed a quantitative method with data collected throught the distribution of questionnaires. The sample consisted of 33 respondents selected using purposive sampling from employees of RSUD Otanaha. Data were analyzed using multiple linear regression with IBM SPSS for Windows Version 23. The results of the study indicate that: (1) Utilization of Information Technology has a positive and significant influence on the Quality of Financial Statements; (2) Internal Control has a positive and significant influence on the Quality of Financial Statements; and (3) Utilization of Information Technology and Internal Control simultaneously have a positive and significant influence on the Quality of Financial Statements at RSUD Otanaha. Keywords: Utilization of Information Technology, Internal Control, Quality of Financial Statements